There and Back: An Interview with Tom Hubbard - Dósa, Attila (Hungarian Journal of English and American Studies, 2021)
In this interview, conducted during the fourteenth ESSE Conference at Brno in the Czech Republic, Scottish academic and writer Tom Hubbard speaks about his recent work of poetry and fiction, such as The Flechitorium (2017) and Slavonic Dances (2017). He also discusses the stimulating forces behind and the stumbling blocks on the long road towards Scottish independence. He fears and is anxious about the consequences of Brexit on the multifaceted exchange in the arts and literature that Scots have been keen to maintain with other nations throughout the centuries. At the center of his discussion lies his view of Scotland’s place in a nexus of international exchange that would be, ideally, based on mutual and informed interest in each other’s cultural achievement—in literature, music, and the visual and performing arts. (AD)